Joint online distance learning to complement postgraduate pathology training in preparation for national board examinations - de Leng, Bas (BMJ Publishing Group, 2025)
Aims To meet the flexible learning needs of pathology residents preparing for national board examinations, a joint distance learning approach was developed using both asynchronous and synchronous activities with whole slide images, drawing on empirical educational research on online distance learning.
Methods In a case study of an implementation of the designed joint distance learning approach with a geographically dispersed group of pathology residents in Finland, the participants' perceptions were measured with a 12-item questionnaire covering the value of the learning opportunity, the quality of the sociocognitive processes and their emotional engagement and social cohesion. Communication during the online session was also recorded and analysed to provide objectivity to the self-report data.
Results The effectiveness of joint online learning for knowledge acquisition and preparation for national board examinations was highly rated. However, despite strong emotional engagement during synchronous activities, participants reported minimal interpersonal interaction, which was also reflected in the recordings of the online session.
Conclusion Using a technology integration framework and guided by the principles of self-determination theory, joint distance learning is emerging as a beneficial addition to postgraduate pathology programmes in preparation for national examinations. However, to realise the full potential of interpersonal interaction, participants should be prepared for an appropriate mindset.